The link between gut microbiota and multiple sclerosis from the perspective of barrier function - Ren, Jingru; Niu, Zhenyu; Wang, Jianchun; Guo, Jing; Hao, Hongjun; Gao, Feng; Liu, Ran; Wang, Zhaoxia (Frontiers in Immunology, 2025)
Recently, more and more studies have begun to focus on the role of gut microbiota in neurological diseases, especially immune-mediated disorders including multiple sclerosis (MS). The bidirectional communication between the gut microbiome and the central nervous system (CNS) is known as the gut-brain axis, which includes two key barriers, namely blood-brain barrier (BBB) and the gut barrier, and has become a crucial framework for understanding the pathophysiological mechanisms of various neurological disorders. Gut microbes co-evolved with humans and play important roles in maintaining steady state via various pathways, including immune regulation. An altered gut microbiota, referred to as dysbiosis, not only induces increased intestinal permeability locally, but also promotes systemic immune responses in the CNS. Increased BBB permeability has been considered the core mechanism for MS, and a “leaky” gut has also been reported in MS as well as its animal models. Therefore, the gut-brain axis is increasingly being considered as playing a crucial role in the pathogenesis of MS, with a major focus on specific gut microbiota alterations associated with the disease. Here, we review how the possible dysfunction of the gut-brain axis might impact MS, with particular emphasis on the barrier function.